Urgensi Pembahasan Taubat dalam Perspektif Hadis - muhammad nurbani (Jurusan Ilmu Hadis Fakultas Ushuluddin, Dakwah dan Adab UIN Sultan Maulana Hasanuddin Banten, 2019)
Humans are not beings who avoid mistakes and sin like an angel. And of course everyone has made a mistake. There is no one in this world who is free from mistakes. Therefore, God opens the door to repentance as much as possible for servants or people who regret and realize the mistakes they have made. Even though there are people who are free from sin